Extraction and Assessment of Peptide Profiles Based on Hydrolysates of Collagen-containing Fish Raw Materials - E. E. Kuprina; E. I. Kiprushkina; Y. V. Broyko; I. A. Shestopalova; M. M. Shamtsyan; O. V. Volkova; N. Y. Romanenko; O. Y. Mezenova; T. Grimm; T. Mörsel (Research Perspective on Biological Science Vol. 1, 2025)
The fish processing industry generates more than 60% of its by-products as waste. These large volumes of fishery by-products will create serious pollution and disposal problems in both developed and developing countries. Experimental studies of fish cutting waste—scales and skin were carried out, their general biochemical composition was studied, a high content of collagen was established, and elastin was noted, which accounted for 76–86% of the protein mass. Processes for the hydrolysis of secondary fish raw materials have been developed: fish scales and skin. Technological schemes have been developed, and the influence of the conditions of thermal, enzymatic, enzymatic-thermal, electro-chemical hydrolysis on the amino acid composition and molecular weight distribution (MWD) and antioxidant activity of peptides and proteins in the obtained hydrolysates has been studied. Statistical data processing was performed using the Microsoft Office 2010 and Mathcad 2000 Professional software packages at a 95% confidence level. It has been established that the enzymatic and enzymatic-thermal method of hydrolysis of fish scales using the enzyme Alcalase 2.5 L and the electrochemical hydrolysis of the skin of cod, trout and herring made it possible to obtain protein hydrolysates with a protein content of 80–90%. At the same time, 91–98% of enzymatic hydrolysates from scales and 62%, 74% and 82.5% of electrochemically obtained hydrolysates from the skin of trout, herring, and cod, respectively, account for the share of low-molecular peptides with a molecular weight of less than 10 kDa. The prospects of their use in functional foods and oil-containing products are noted.